The Human Amniotic Mesenchymal Stem Cells (hAMSCs) Improve the Implant Osseointegration and Bone Regeneration in Maxillary Sinus Floor Elevation in Rabbits - Lu Yin; Zhi-xuan Zhou; Ming Shen; Ning Chen; Fei Jiang; Shou-Lin Wang (Stem Cells International)
Insufficient bone height in the posterior maxilla is a challenging problem in dental implantation. Bio-Oss, though routinely used in maxillary sinus floor elevation (MSFE), is not osteoinductive. Human amniotic mesenchymal cells (hAMSCs) isolated from placental tissues have potential for multidifferentiation and immunomodulatory properties and can be easily obtained without the need for invasive procedures and without ethical concerns. This is the first study to use hAMSCs to improve implant osseointegration and bone regeneration after MSFE. Human AMSCs were loaded into a fibrin gel and injected into rabbit MSFE models. The rabbits were assigned to four groups (n=3 per group), i.e., the control group, the hAMSC group, the Bio-Oss group, and the hAMSC/Bio-Oss group. The animals were sacrificed at postsurgery for four and twelve weeks and evaluated by histology and immunohistochemistry. Bone volume, bone volume/tissue volume, bone-to-implant contact ratio, and vessel-like structures in the hAMSC/Bio-Oss group were significantly better than those in other groups in the peri-implant and augmented areas. Immunofluorescence staining showed that alkaline phosphatase (ALP) activities of two hAMSC groups were higher than those of the other two groups. Sequential fluorescent labeling was performed in all of the 12-week groups. Observations showed that hAMSCs accelerated mineralized deposition rates on implant surfaces and in bone-augmented areas. These data demonstrated that hAMSCs could enhance implant osseointegration and bone regeneration after MSFE and might be used to optimize dental implantation in the future.